Diabetic Retinopathy Prevalence in Patients with Established Diabetes Mellitus:A tertiary Care Hospital Study - Muhammad Junaid Sethi, Umer Khan, Natasha Junaid, Nazli Gul, Ishan Ullah, Muhammad Israr (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetic retinopathy is one of the microvascular consequences of this metabolic disorder. Objectives: To establish a clear conclusion on the Prevalence of diabetic retinopathy in those who have already been diagnosed with diabetes. Methods: This was a tertiary care hospital study performed at the Peshawar ophthalmology outdoor clinic. The research period for this article was from 01 June 2020 to 05 December 2020. Male and female patients with diabetes mellitus comprised 86 participants in this research. Fundoscopy was performed on all patients in the medical clinic to check for diabetic retinopathy. Results: average age was 55.099±6.20 years, the Duration of diabetes was 09.29±03.62 years, and the average weight was 85.061±07.55Kg. There were 67% male patients and 33% female ones One-third of diabetic patients were found to have retinopathy. Conclusion: Diabetic retinopathy, length of time with diabetes, and diabetes mellitus are all relevant terms. Keywords: diabetes retinopathy, diabetes mellitus, Duration of diabetes